1981
DOI: 10.1149/1.2127439
|View full text |Cite
|
Sign up to set email alerts
|

Application of Wagner's Theory to the Parabolic Growth of Oxides Containing Different Kinds of Defects: I . Pure Oxides

Abstract: Table V. Enthalpies of sublimation of zirconium iodides* AH~s (subl) kcal/mol ZrI 130 ZrI~ 99 ZrI8 63 ZrI, 31.9 * Values are hypothetical because all the iodides, except ZrI~, vaporize incongruently to ZrI,(g), see text.tri-iodides intermediate, in keeping with the relative values of their sublimation enthalpies, which dominates the entropy at those lower temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
(163 reference statements)
1
16
0
Order By: Relevance
“…The treatment presented here is based on the same theoretical framework as was developed in previous papers for the parabolic growth of pure oxides (15) or uniformly doped oxides (1) during the high temperature oxidation of pure metals or dilute alloys. As shown there, the concentration of each type of lattice and electronic defect is fixed at any point in the scale by the local values of the oxygen activity and impurity concentration through the local electroneutrality condition.…”
Section: Theorymentioning
confidence: 99%
“…The treatment presented here is based on the same theoretical framework as was developed in previous papers for the parabolic growth of pure oxides (15) or uniformly doped oxides (1) during the high temperature oxidation of pure metals or dilute alloys. As shown there, the concentration of each type of lattice and electronic defect is fixed at any point in the scale by the local values of the oxygen activity and impurity concentration through the local electroneutrality condition.…”
Section: Theorymentioning
confidence: 99%
“…In the presence of Li in substitutional positions in MO, in addition to the usual equations for the formation of the different lattice defects (1), the mechanism of incorporation of the impurity in a normal lattice site according to the reaction (17) Yz 02 + Li20 = 2Li' + 2h" + 20 x [1] must also be considered. Equation [1] shows that the introduction of Li in MO produces an increase in the concentration of the electron holes: this in turn will lower the concentration of the charged metal vacancies or raise that of the charged metal interstitials in oxides containing only one kind of defect, but will affect simultaneously both concentrations in the case of oxides having both kinds of defects, according to Eq. [9]- [10] and [12]-[13] of PartI (1).…”
Section: Theorymentioning
confidence: 99%
“…In a previous paper [Part I (1)] we have examined the oxidation behavior of pure metals forming electronically semiconducting oxides with a complex defect structure, extending KrSger's approach (2) to Wagner's theory of parabolic oxidation (3) and considering oxides in which only metal diffusion is important. We extend here the same analysis to the growth of doped oxides on dilute alloys, so that only the base oxide is formed in the process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Five years later, Arnold and Koonce introduced a method to create metal oxide filaments by annealing the corresponding metals (e.g., platinum, zinc, nickel, palladium, lead, iron, and magnesium) at 300–700 °C in air . Afterward, this research topic attracted the extensive interest of scientists. With the development of nanoscience and nanotechnology, Jiang et al. found that CuO nanowires can be easily synthesized by heating copper substrates, for example, grids, foils, and wires, at 400–700 °C in air .…”
Section: Introductionmentioning
confidence: 99%